Effectiveness of an educational program to reduce parenting stress and improve coping mechanism among parents of children with autism spectrum disorder in Jordan - El-Salam, Al-Oran Haytham Mohammad Abd (2020)
Parents of children with Autism Spectrum Disorder are prompt to frustration and anxiety due to different stressors and demands over time. This needs to be prioritized in healthcare strategies to maintain the health well-being of parents and to enhance their ability to cope with stress. The general objective of this study was to develop, implement, and evaluate the effectiveness of the educational program on the parenting stress (including parental distress, parent-child dysfunctional interaction and difficulty of the child) and the coping mechanism (including problem-focused coping and emotion-focused coping) among parents of children with Autism Spectrum Disorder in Amman, Jordan. A single-blinded, cluster randomized controlled trial was conducted to compare the intervention group versus an active control group. A total of 211 eligible parents were included in this study. Chi-square test and Fisherʼs exact test (for categorical data) and independent t-test (for continuous data) were used to assess equivalence between the intervention and control groups at the baseline. Repeated Measures MANOVA was conducted on the parenting stress and the coping mechanism. The mean age of participants was 35.8 years (SD = 4.6), 48.3 % were fathers; while 51.7 % were mothers and they were Muslims (100%). The majority of them were married (97.2 %), employed (71.6 %) with Bachelor's education (44.5%). There were no significant differences in the socio-demographic (p-value < .05) and dependent variables between the intervention and control groups before the intervention (p-value < .05). There were significant main effects for the group (p = .038, p = .002, p < .001), time (p < .001, p < .001, p < .001) and group by time interaction (p <.001, p < .001, p <.001) for the parent distress, the difficult child and problem-focused coping respectively. The analysis indicated a significant effect of time on the parent-child dysfunctional interaction and emotion-focused coping (p < .00, p < .001) and interaction between the group and time (p < .001, p < .001), but not for the group (p = .250, p = .140 ). This study provided empirical support for the effectiveness and feasibility of the educational program in reducing parenting stress and improving the coping mechanism and should be encouraged for its application in the additional setting and studied further for its effectiveness.